Research on the application of vertical axis wind turbine in subway tunnel. Issue 1 (1st December 2022) - Yu, Xin; Wang, Zheng; Xiang, Pei
Abstract: When the subway train is running at high speed in the tunnel, the originally still air in the tunnel is pushed by the train, so that the air in the tunnel is immediately accelerated, and in the same direction as the train travels, which is called the piston effect in the tunnel, also known as Piston wind. The wind speed of the piston wind in the tunnel is 7 9m/s, and the air volume is considerable. The vertical axis wind turbine has the characteristics of small size, low starting wind speed and high wind energy utilization rate, so it can use piston wind to generate electricity to supply power to lighting equipment and advertising lights in the tunnel, so as to achieve the purpose of energy saving and emission reduction.